Edukasi Hukum bagi Remaja: Menanggulangi Risiko dan Dampak Judi Online - Taufik, Zahratul'ain; Nirmala, Atika Zahra; Susilawati, Ika Yuliana; Dudy, Aryadi Almau; Rahmania, Nunung; Ahwan Ahwan (Universitas 45 Surabaya, 2025)
In the modern era, technology and the internet have become inseparable parts of human life, especially for teenagers. While digital connectivity offers easy access to information and communication, it also brings serious risks—one of which is online gambling. Teenagers are particularly vulnerable due to their constant engagement with technology and the appeal of online gambling, which offers easy access, attractive bonuses, and low entry costs. This activity can lead to harmful consequences, including addiction, psychological distress, and financial problems. The Indonesian government has taken legal measures to curb online gambling through various regulations, such as the Criminal Code, Law No. 7 of 1974 on the Control of Gambling, and the Electronic Information and Transactions Law (ITE Law), which imposes criminal sanctions on offenders. However, despite ongoing efforts to block gambling sites, new ones continue to emerge. Therefore, effective legal education is essential to raise teenagers’ awareness of the dangers and legal consequences of online gambling. Collaboration among schools, families, and communities plays a vital role in nurturing legal understanding and protecting young people from engaging in online gambling, ensuring they are equipped with knowledge that safeguards their future.